The Relationship Between Cancer-Related Worry and Posttraumatic Growth in Adolescent and Young Adult Cancer Survivors - McDonnell, Glynnis A. (Psychooncology, 2018)
OBJECTIVES: To examine cancer-related worry in adolescent and young adult (AYA) cancer survivors and its relationship with posttraumatic growth over time, as the relationship between these constructs has not been assessed longitudinally in this population. METHODS: 153 AYA cancer survivors completed measures of cancer-related worry and posttraumatic growth three times across approximately one year. Descriptive statistics were calculated for cancer-related worry items, and mixed-effects modeling assessed the relationship between cancer-related worry and posttraumatic growth. RESULTS: Most participants reported at least moderate cancer-related worry in at least one area at each assessment (88.2-93.9% across time points). Worry about future health was the most prevalent concern (65.4%-83.7% across time points). Cancer-related worry was positively related to posttraumatic growth in the mixed-effects model. However, post hoc analyses indicated that cancer-related worry and posttraumatic growth were modestly related; there was no evidence that either construct predicted the other over time. CONCLUSIONS: Cancer-related worry appears to be a common psychosocial outcome in AYA cancer survivors. However, cancer-related worry appears to be only modestly related to the development of posttraumatic growth, implying that these may be independent constructs despite theoretical literature suggesting that posttraumatic growth may stem from posttraumatic distress. Thus it is necessary to assess AYA survivors for cancer-related worry and posttraumatic growth, and develop interventions to target cancer-related worry and foster posttraumatic growth.